Complete endoscopic removal of Maxillary Odontogenic Keratocyst: A case report - Shashikant Anil Pol; Surinder K Singhal; Nitin Gupta; Shalima PS; Himanshu C Bayad (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Objective: To present a rare case of endoscopic removal of maxillary Odontogenic Keratocyst in a paediatric patient. Case report: We are presenting the case of a 9 year old male, with chief complaint of swelling on right side of face for 5 months. It was not associated with decrease in vision or diplopia. On examination there was a single swelling of size 4×3 cm on right side of cheek, with smooth surface and firm consistency. Non Contrast Computed Tomography of nose and paranasal sinus showed expansile fluid density lesion completely filling right maxillary sinus with impacted tooth in superior part along the roof of maxillary sinus. Cyst wall with impacted tooth was removed completely by endoscopic approach without any need for Caldwell approach. Final histopathological report was odontogenic keratocyst. Patient is on regular follow up and is asymptomatic till date without any recurrence. Conclusion: Odontogenic keratocyst should be considered as one of the differential diagnoses in any cystic swelling involving maxilla and mandible. CT scan is the main diagnostic modality to see the exact location and extent and also helps in planning the surgical approach. Endoscopic approach provide excellent surgical outcome with preservation of normal anatomy. Long term surveillance is required to look for any recurrence.